(untitled) (Nordic Journal of African Studies, 2010)
Tanzania is a multilingual country with 150 ethnic languages spoken within its boundaries. However, Kiswahili is the language most frequently used in government offices, as well as in everyday activities countrywide. Despite the adoption of one of Africa’s largest languages as an official language, the government has constantly insisted that English should remain the only medium of instruction at post-primary level, because of its tremendous power and prestige in the global market. The government’s stance reveals a limited understanding of what a system of promoting bilingualism and bi-literacy in education should involve. This paper presents the findings on a study conducted in primary and secondary schools in Tanzania with regard to language-in-education policy implementation. Therefore, the practice in schools is that monolingual education dominates and the idea of bilingual education appears far-fetched to practioners in the education sector. This paper proposes the 50–50 Model as a way forward for implementing strong bilingual education in Tanzania.